2021
DOI: 10.3390/ijerph18168292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oral Health Care Systems on Future Career Environment of Dental Students in Europe

Abstract: Oral healthcare is organized subsidiarily and independently by nation states in Europe and also within the EU and consequently, major differences between the nation states and the various oral healthcare systems in Europe are present. The socialization in the respective catchment area can have an impact on the job choice and the perception of employment opportunities of different professional groups. Therefore, the purpose of this survey was to elucidate the influence of different oral healthcare systems on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…20 Additionally, a European study showed that dental students aspire to become practitioners and establish their practices. 21 In Indonesia, the study of career choice was conducted on final-year medical students. 13 However, survey research conducted on students of the faculty of dentistry has not been made yet.…”
Section: Introductionmentioning
confidence: 99%
“…20 Additionally, a European study showed that dental students aspire to become practitioners and establish their practices. 21 In Indonesia, the study of career choice was conducted on final-year medical students. 13 However, survey research conducted on students of the faculty of dentistry has not been made yet.…”
Section: Introductionmentioning
confidence: 99%